Benefits and risks: Views of humanitarian organizations in Lebanon on corporate assistance. - Jihad Makhoul; Catherine El Ashkar; Melissa Mialon; Anna Levy; Diana Sabbagh; Rima Nakkash (Public Library of Science (PLoS), 2023)
Compounding humanitarian and political crises within and across countries have been met with shrinking public resources for coordination, recovery, and mitigation. This resource constrained humanitarian environment presents opportunities for multinational corporations to supplement budgets and actively participate in new markets through connecting with humanitarian work. Given the well-established influence of corporations on public health, an assessment of industry funding to humanitarian assistance is necessary especially in the fragile context of Lebanon with a substantial refugee population and multiple compounding crises. This paper examines three aspects of corporate assistance in humanitarian crises in Lebanon. It investigates the modality of corporate assistance to humanitarian agencies, the extent to which humanitarian agency staff are aware of implications of this assistance along with any ethical considerations related to it, and both the risks and benefits for corporations and people. This study explores the views of 14 local and international humanitarian agencies in Lebanon) through in-depth interviews conducted between 2020 and 2022. Interviews were recorded, transcribed and subject to thematic analysis. All agencies participating in the study provided social and health assistance as well as education, vocational training, and other services to refugees or Lebanese. Findings indicate that the majority of them receive corporate funding in varying amounts and in-kind contributions to support various projects. Despite imposed conditions by the corporations, such as posting logos and stories, the agencies perceived the benefits of partnering, mentioning financial assistance in time of need, and flexible agendas that outweigh the risks of conflicts of interest of corporate branding on the populations they serve. Benefits to the corporations themselves relate to corporate social responsibility, increased market reach and visibility. Challenges in partnering with for-profits include ethical considerations and programmatic issues, however no guidelines were reported to exist to detect corporate conflicts of interest, instead most of the agencies rely on their value systems for screening.